Understanding Female Motivation in Choosing Computer Science and Information Technology: A Narrative Study from Nepal - Subba , Ganga; Luitel, Bal Chandra (NPRC Journal of Multidisciplinary Research, 2025)
In today's technologically advanced world, the underrepresentation of women in Computer Science and Information Technology programs remains a primary worldwide concern, including in Nepal. This study sought to explore the motivations of female students pursuing undergraduate degrees in Computer Science and Information Technology by analyzing their stories guiding their decisions. The Narrative inquiry technique within the qualitative research method was employed to examine how their motivation developed from childhood to the time they enrolled. Six female students who chose Computer Science and Information Technology (CSIT) at their bachelor's degree level were selected from two different colleges in two distinct areas, and in-depth interviews were conducted. Maslow's Hierarchy of Needs Theory directed the research. Findings revealed that extrinsic motivators such as job prestige and financial incentives had a stronger influence than intrinsic motivators, with participants frequently citing career stability and social recognition as key factors. Family encouragement, early exposure to technology, and the presence of inspiring role models also played a significant role in shaping their interest. While the study offers rich, contextual insights, it is based on a small sample size, and its findings are not meant to be generalized. Rather, the study aims to illuminate individual experiences and inform gender-inclusive strategies in education and policymaking. Promoting female visibility in the ICT sector is critical to inspiring more women to enter and thrive in the field.